Internalization of Religious Tolerance Values through Islamic Religious Education in Multicultural Schools - Indra Wijaya; Fathul Jannah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the internalization of religious tolerance values in Islamic Religious Education at SMP Negeri 8 Samarinda and SMP Negeri 1 Bontang. The research employed a qualitative multisite approach involving observations, in-depth interviews, and documentation techniques. The participants included Islamic Religious Education teachers, school principals, vice principals, and students from diverse religious backgrounds. Data were analyzed using interactive analysis techniques through data reduction, data display, and conclusion drawing. The findings reveal that the internalization of tolerance values was implemented through contextual learning, teacher exemplification, habituation activities, multicultural interaction, and inclusive school culture. Islamic Religious Education teachers integrated values of justice, empathy, equality, and peaceful coexistence into classroom instruction and daily social interaction. Teachers also functioned as moral role models who demonstrated inclusive attitudes toward students from diverse religious backgrounds. Habituation programs such as collaborative extracurricular activities, social service, and school cultural programs strengthened students’ awareness of diversity and social harmony. Supporting factors included teachers’ commitment, positive school culture, and multicultural interaction among students, while inhibiting factors involved social media influence, exclusive family environments, and limited instructional time. The study concludes that tolerance education becomes more effective when cognitive understanding, social interaction, and moral exemplification are integrated simultaneously within educational practices. Therefore, schools play strategic roles in strengthening multicultural harmony and preventing intolerance among students in pluralistic societies